Determinasi Motivasi Kerja, Kompetensi, Pelatihan dan Kepuasan Kerja terhadap Kinerja Karyawan - Titi Hasanah; Markus Markus (IPM2KPE, 2023)
The aims of the research are, a) to analyze the level of encouragement of work motivation, competence, training, and job satisfaction on performance; b) analyze the influence of work motivation, competency, training, and job satisfaction simultaneously on employee performance at PT Ansaf Inti Resources. The research method used is a survey research method. Respondents were 83 employees of PT Ansaf Inti Resources. This type of research is explanatory research. Data collection was carried out through questionnaires and company documents. Data analysis using multiple regression analysis. The results showed, a) based on the t test, the work motivation variable (Xl) had a significance value of 0.022 <0.05 and a positive coefficient value of 1 of 0.099 had a significant positive effect on performance (Y); b) based on the t test, the competency variable (X2) has a significance value of 0.000 <0.05 and a positive 2 coefficient value of 0.591 has a significant positive effect on performance (Y); c) based on the t test, the training variable (X3) has a significance value of 0.049 > 0.05 and a positive coefficient value of 0.067 and has a significant positive effect on performance (Y); d) based on the t test, the job satisfaction variable (X4) has a significance value of 0.000 > 0.05 and a positive coefficient value of 0.313 and has a significant positive effect on performance (Y). Conclusion, a) motivational variables affect employee performance; b) the variable competence with motivation has a significant effect on employee performance; c) the variables of training along with motivation and competence have a significant effect on employee performance; d) the variables of job satisfaction together with motivation, competency, training and job satisfaction have a significant effect on employee performance Keywords: Job Satisfaction, Employee Performance, Competence, Work Motivation, Training